Design of A Microchip Optical Switching Driven by Low Direct-current Voltage - Dedi Irawan (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
A microchip optical switching based on a directional fiber coupler has been successfully fabricated by using silicon-on-insulator with two steps of photolithography and dry etching methods. Each waveguide has 1.75 µm width, 2 µm high and the distance between the waveguides at the coupling region was 2 µm. Metal aluminum layer with 4 µm width was attached at the coupling region due to switch the optical signal from a waveguide to another. The coupled mode theory was determined to model the coupling power at the coupling region. Experimental results have shown a good agreement of   switching   power   at   the   coupling   as   function   of increment of direct current voltage. It has been obtained that to switch the signal described by the switching region that occurs for the applied DC voltage in range of 18 volt to  32  volt.  Certainly,  an  adjustable  optical  switching driven by low direct current voltage promises wide range of   its   application   in   optical   network   and   sensor application.